Collective action: The case of promoting integrity and accountability in small and medium enterprises - Oplas, Ma. Ella C. (Animo Repository, 2013)
The Small and Medium Enterprises (SMEs) play an important role in the Philippine economy. They comprise 99.6% of the business, employ 63.2% of the labor force and contribute 35.7% of total sales and value added in the country. The SMEs are also the most prone sector to corruption. In the 2011-2012 World Economic Forum Global Competitiveness Report, it was cited that the most problematic factors for doing business in the Philippines is corruption. It has become normal to hear SMEs complain about public servants asking for "grease" money to facilitate transactions. It cannot also be discounted that corruption exists because there are SMEs that initiates them. This case study focuses on the initiative by the hills Program on Governance, Ramon V. del Rosario, Sr. - C.V. Starr Center for Corporate Governance of Asian Institute of Management. The initiative aims to strengthen awareness and understanding of the social and economic costs of corruption among Philippine businesses and to generate their support for anti-corruption efforts and to strengthen the ability of SMEs to prevent corrupt and other unethical behaviour among their employees. The initiatives is anchored on the fact that SMEs have an important role to play in combating corruption. They can either be victims, initiators or active participants against corruption. It highlights the importance of SMEs coming together for capacity building and consultation to formulate strategies for combating corruption in business. It likewise gives importance to the role of the government in SME development and promoting integrity and accountability in business.